Acelaração do universo e criação gravitacional de matéria escura fria: novos modelos e testes observacionais - Silva, Francisco Edson da (2008)
Recent astronomical observations (involving supernovae type Ia, cosmic background radiation anisotropy and galaxy clusters probes) have provided strong evidence that the observed universe is described by an accelerating, flat model whose space-time properties can be represented by the FriedmannRobertsonWalker (FRW) metric. However, the nature of the substance or mechanism behind the current cosmic acceleration remains unknown and its determination constitutes a challenging problem for modern cosmology. In the general relativistic description, an accelerat ing regime is usually obtained by assuming the existence of an exotic energy component endowed with negative pressure, called dark energy, which is usually represented by a cosmological constant ¤ associated to the vacuum energy density. All observational data available so far are in good agreement with the concordance cosmic ¤CDM model. Nevertheless, such models are plagued with several problems thereby inspiring many authors to propose alternative candidates in the relativistic context. In this thesis, a new kind of accelerating flat model with no dark energy and fully dominated by cold dark matter (CDM) is proposed. The number of CDM particles is not conserved and the present accelerating stage is a consequence of the negative pressure describing the irreversible process of gravitational particle creation. In order to have a transition from a decelerating to an accelerating regime at low redshifts, the matter creation rate proposed here depends on 2 parameters (y and ß¯): the first one identifies a constant term of the order of H0 and the second one describes a time variation proportional to he Hubble parameter H(t). In this scenario, H0 does not need to be small in order to solve the age problem and the transition happens even if there is no matter creation during the radiation and part of the matter dominated phase (when the ß term is negligible). Like in flat ACDM scenarios, the dimming of distant type Ia supernovae can be fitted with just one free parameter, and the coincidence problem plaguing the models driven by the cosmological constant. ACDM is absent. The limits endowed with with the existence of the quasar APM 08279+5255, located at z = 3:91 and with an estimated ages between 2 and 3 Gyr are also investigated. In the simplest case (ß = 0), the model is compatible with the existence of the quasar for y > 0:56 whether the age of the quasar is 2.0 Gyr. For 3 Gyr the limit derived is y > 0:72. New limits for the formation redshift of the quasar are also established